2022
DOI: 10.1186/s12958-022-00907-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns are associated with improved ovarian reserve in overweight and obese women: a cross-sectional study of the Lifestyle and Ovarian Reserve (LORe) cohort

Abstract: Background Growing evidence suggests that adherence to certain dietary patterns is associated with improved fecundity and reproductive outcomes in the general population and infertile couples assisted reproductive treatments. The objective of this study was to assess if dietary patterns are associated with ovarian reserve in reproductive age women without a history of infertility. Methods This was a cross-sectional study of 185 women in the Lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…In a prospective study on the association between dietary intake and rate of AMH decline among eumenorrheic women from the Tehran Lipid and Glucose study, it was shown that the consumption of dairy food reduced the rate of AMH decline in these women (29). Eskew et al (8) conducted a cross-sectional study on 185 overweight and obese women without a history of infertility from the Lifestyle and Ovarian Reserve (LORe) cohort and found that greater adherence to a profertility diet, characterized by increased intake of whole grains, soy, seafood, dairy, low pesticide residue fruit and vegetables, and supplemental vitamin D, folic acid and B12, was associated with higher AMH level and AFC. Also, low preconception Mediterranean diet score (MDS) was reported to be a risk factor for poor ovarian response in a study on 296 women seeking infertility treatments (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective study on the association between dietary intake and rate of AMH decline among eumenorrheic women from the Tehran Lipid and Glucose study, it was shown that the consumption of dairy food reduced the rate of AMH decline in these women (29). Eskew et al (8) conducted a cross-sectional study on 185 overweight and obese women without a history of infertility from the Lifestyle and Ovarian Reserve (LORe) cohort and found that greater adherence to a profertility diet, characterized by increased intake of whole grains, soy, seafood, dairy, low pesticide residue fruit and vegetables, and supplemental vitamin D, folic acid and B12, was associated with higher AMH level and AFC. Also, low preconception Mediterranean diet score (MDS) was reported to be a risk factor for poor ovarian response in a study on 296 women seeking infertility treatments (30).…”
Section: Discussionmentioning
confidence: 99%
“…We used analysis of covariance (ANCOVA) to compare adjusted (for FM, BMI, Physical activity and total energy) means of AMH and AFC across the DQI-I quartiles. Potential confounding variables included in the analyses were chosen based on prior literature (8,25) as well as Directed Acyclic Graph (DAG) (26). The multivariate logistic regression analysis was conducted to evaluate the association between quartiles of DQI-I score and the odds of DOR, as well as between one-unit increase in DQI-I score and DOR risk, after adjustment for multiple covariates in three models.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that females of the same age have various reproductive potential may indicate the impact of environmental factors on ovarian reserve [ 4 ]. Identifying potentially modifiable factors including nutritional factors which could promote ovarian reserve and thus beneficially affect fertility has been the focus of several recent observational studies [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%